WASP-92b, WASP-93b and WASP-118b: three new transiting close-in giant planets - Hay, K. L. (2016)
We present the discovery of three new transiting giant planets, first detected with the WASP telescopes, and establish their planetary nature with follow up spectroscopy and ground-based photometric light curves. WASP-92 is an F7 star, with a moderately inflated planet orbiting with a period of 2.17 d, which has Rp = 1.461 ± 0.077RJ and Mp = 0.805 ± 0.068MJ. WASP-93b orbits its F4 host star every 2.73 d and has Rp = 1.597 ± 0.077RJ and Mp = 1.47 ± 0.029MJ. WASP-118b also has a hot host star (F6) and is moderately inflated, where Rp = 1.440 ± 0.036RJ and Mp = 0.514 ± 0.020MJ and the planet has an orbital period of 4.05 d. They are bright targets (V = 13.18, 10.97 and 11.07, respectively) ideal for further characterization work, particularly WASP-118b, which is being observed by K2 as part of campaign 8. The WASP-93 system has sufficient angular momentum to be tidally migrating outwards if the system is near spin–orbit alignment, which is divergent from the tidal behaviour of the majority of hot Jupiters discovered.